AB0977 Biomechanical factors and physical examination findings in osteoarthritis of the knee: Associations with tissue abnormalities assessed by conventional radiography and by high resolution magnetic resonance imaging. (23rd January 2014) - Knoop, J.; Dekker, J.; Klein, J.-P.; van der Leeden, M.; van der Esch, M.; Reiding, D.; Voorneman, R.E.; Gerritsen, M.; Roorda, L.D.; Steultjens, M.P.; Lems, W.F.
Abstract : Background: Although biomechanical factors of the knee joint like muscle strength, proprioceptive accuracy and laxity play an important role in knee osteoarthritis (OA), only limited evidence exists on associations with specific tissue abnormalities. Furthermore, findings from physical examination have never been studied in relation to tissue abnormalities of the knee joint. Objectives: To explore associations between tissue abnormalities assessed by conventional radiography and high resolution MRI, biomechanical factors and physical examination findings in patients with knee OA. Methods: Explorative cross-sectional study in 105 patients with knee OA. Knees were imaged using radiography and 3.0 Tesla MRI. Multivariable regression analyses were used to explore associations between tissue abnormalities, visualised by radiography or MRI, biomechanical factors (quadriceps and hamstrings muscle strength, proprioceptive accuracy and varus-valgus laxity) and physical examination findings (bony tenderness, crepitus, bony enlargement and palpable warmth). Results: MRI based synovitis, MRI based cartilage loss and radiographic based joint space narrowing were found to be associated with quadriceps weakness. Radiographic features (joint space narrowing and osteophyte formation) were related to varus-valgus laxity. Multiple tissue abnormalities, but only those detected by MRI, were associated with physical examination findings (crepitus and palpable warmth). Neither MRI features nor radiographic features were found to be associated with hamstrings muscle strength, proprioceptive accuracy, bony tenderness and bony enlargement. Conclusions: In conclusion, a discordance between tissue abnormalities, biomechanical factors and physical examination findings in knee OA was observed, for both conventional radiography and high resolution MRI. Relevant new findings include a highly significant association between MRI based synovitis and quadriceps weakness and a superiority of MRI over conventional radiography in association with physical examination findings. Disclosure of Interest: None Declared